SOSIALISASI DAN PELATIHAN PENGGUNAAN SISTEM OUTCOME BASED EDUCATION (OBE) DALAM PENGELOLAAN PEMBELAJARAN - Mukhroji (Jurnal Pengabdian Pemersatu Bangsa, 2025)
The socialization and training activity on the Outcome Based Education (OBE) system was conducted on November 19, 2025, at the Programming Laboratory of Universitas Bina Bangsa Getsempena, attended by 100 lecturers from various study programs. The activity aimed to enhance lecturers' understanding and skills in implementing a learning curriculum based on learning outcomes. Methods included lectures, demonstrations, hands-on practice, discussions, and mentoring, enabling participants to grasp both theory and practice of OBE. Evaluation was conducted through pre-test and post-test, observation of system usage, and participant satisfaction questionnaires. The results showed an increase in average participant scores from 58.40 in the pre-test to 84.70 in the post-test, an improvement of 45.03%, indicating the effectiveness of the training. Furthermore, 82% of participants were able to use the OBE system independently, while 88% and 85% were able to correctly organize learning outcomes and assessment indicators. Satisfaction surveys revealed 90% satisfaction with materials, 92% with instructors, 87% with facilities, and 89% with mentoring. This activity demonstrates that OBE socialization and training effectively improve lecturers’ competencies, strengthen understanding of OBE concepts, and support the implementation of an outcome-based curriculum. Continuous training is recommended to ensure sustained OBE implementation